Pseudoastrosphaeriellopsis mangrovei sp. nov. (Pleosporales, Pseudoastrosphaeriellaceae) a novel marine fungal species from Indian Mangroves - Rakshit, Shovan; Chanda, Prakriti; Sarma, V. V. (Phytotaxa, 2026)
Mangroves are ecologically important but underexplored ecosystems, especially in terms of fungal diversity and their roles in the decomposition of organic matter. This study presents the identification of a new fungal species of Pseudoastrosphaeriellopsis, isolated from decaying twigs of Avicennia marina in two separate mangrove areas: the Andaman Islands and Tamil Nadu, India. A polyphasic approach was adopted by combining morphological characterisation, molecular phylogenetics, and multi-locus sequence analysis to determine the taxonomic placement of Pseudoastrosphaeriellopsis mangrovei sp. nov. The occurrence of P. mangrovei in geographically separated but ecologically comparable environments indicate a possible adaptation to the saline and anaerobic conditions typical of mangrove ecosystems.